Analysis of KatG Ser315Thr Mutation in Multidrug Resistant Mycobacterium tuberculosis and SLC11A1 Polymorphism in Multidrug Resistance Tuberculosis in Central Development Region of Nepal Using PCR-RFLP Technique: A Pilot Study - Shrestha, Raunak; Joshi, Rubin Narayan; Joshi, Kriti; Poudel, Bal Hari; Shrestha, Bhupal Govinda (Nepal Journal of Biotechnology, 2010)
Ser315Thr mutations in genes encoding the mycobacteria catalase-peroxidase (KatG) has been associated with the major resistance to isoniazid (INH) in Mycobacterium tuberculosis (MTB). Also G/C polymorphisms in INT4 region of the solute carrier family 11 member 1 gene (SLC11A1) and susceptibility towards tuberculosis (TB) has been demonstrated worldwide. 24 drug resistant MTB culture positive samples and 24 whole?blood samples were collected from different TB patients of Central Development Region of Nepal in 2009. A Polymerase Chain Reaction (PCR) - Restriction Fragment Length Polymorphism (RFLP) assay was carried out in order to investigate Ser315Thr KatG mutation and G/C polymorphism in INT4 region. 4 (16.67%) samples out of 24 MTB culture samples demonstrated the Ser315Thr KatG mutation whereas none of the 24 whole blood samples were found to contain G/C polymorphism in INT4. Though no significant correlation could be found between INT4 polymorphism and TB susceptibility, overall scenario of Nepal cannot be drawn from this data. Molecular diagnostic technique such as PCR-RFLP can be used in a robust scale to carry out base line studies in the TB population of Nepal. Key words: Multi?drug resistance; Tuberculosis; PCR; RFLP Nepal Journal of Biotechnology. Jan. 2011, Vol. 1, No. 1 : 14-21